Effect of Financial Performance, Firm Size, and Leverage on Corporate Social Responsibility (Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange) - Willy Tan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Corporate social responsibility is also a company's commitment to the interests of stakeholders in a broad sense other than the interests of the company. This research study is about effect of financial performance, firm size, and leverage on corporate social responsibility, empirical study in Mining Companies listed on the Indonesia Stock Exchange. The population in this study were 28 Mining Companies listed on the Indonesia Stock Exchange in 2013-2017. The total sample used is 85 (5 years x 17). The research used multiple linear regression analysis method. The results showed that financial performance has a significant effect on corporate social responsibility in Mining Companies listed on the Indonesia Stock Exchange. Firm size has no significant effect on corporate social responsibility in Mining Companies listed on the Indonesia Stock Exchange. Leverage has a significant effect on corporate social responsibility in Mining Companies listed on the Indonesia Stock Exchange. Financial performance, firm size, and leverage have a significant effect on corporate social responsibility in Mining Companies listed on the Indonesia Stock Exchange.